Environmental Health Aspect of The Novel Corona Virus Disease and Its Global Impact - Egbo Walamam Mansi (PT Mattawang Mediatama Solution, 2021)
Covid-19 is a severe acute respiratory syndrome (SARS) caused by a zoonotic virus in which bats have been identified as carriers. The disease outbreak was first reported on 1 December 2019, in Wuhan city in the Hubei province of China. It has infected more than eleven million persons worldwide and hundreds of thousands have died from the disease complications. It has spread across over 213 countries and territories globally. The global economic impact of the disease has been monumental. The impact cuts across global stock markets, aviation, tourism, entertainment and sports industries. Politics and governments have equally been impacted upon by the disease as legislative businesses have been suspended as a result of the disease. Many political leaders have tested positive and have got to undergone self quarantine and treatment. This paper have equally identified and itemized environmental health aspects of the disease which include: sneeze, cough, talk, touch and covid-19 control waste materials such as face mask, disposable hand glove, medical apron, used tissue papers. Conclusively, it is recommended that face mask should be produced with materials that will be comfortable to people in order to encourage the use. Disused materials should be disposing of properly and promptly.